Rehabilitation of torture survivors and prevention of torture: Priorities for research through a modified Delphi Study (with Commentaries) - Pérez-Sales, Pau; Witcombe, Nicola; Otero Oyague, Diego (Torture Journal, 2018)
Background: Research is a key element in prevention and in ensuring that survivors of torture have access to appropriate and effective rehabilitation, but it is often neglected as more pressing issues frequently come first. Click on PDF to see full abstract.